Comparison of Aging Performances and Mechanisms: Super-Durable Fire-Resistant “Xuan Paper” Versus Chinese Traditional Xuan Paper - Li-Ying Dong; Ying-Jie Zhu; Jin Wu; Han-Ping Yu (Molecules)
Paper is a thin nonwoven material made from cellulose fibers as the main raw material together with some additives. Paper is highly flammable, leading to the destruction of countless precious ancient books, documents, and art works in fire disasters. In recent years, researchers have made a lot of efforts in order to obtain more durable and fire-retardant paper. Owing to the successful synthesis of ultralong hydroxyapatite (HAP) nanowires as a new kind of inorganic nanofiber material, it becomes possible to develop a new kind of super-durable and fire-resistant paper. Recently, the authors’ research group prepared a new kind of fire-resistant “Xuan paper” consisting of ultralong HAP nanowires. In this article, the super-durable fire-resistant “Xuan paper” based on ultralong HAP nanowires and the traditional Xuan paper based on cellulose fibers were evaluated by the accelerated aging method for 1200 days at 105 °C in air, which is the equivalent of 10,000 years of natural aging in the ambient environment. The aging mechanism of the traditional Xuan paper was further investigated by studying the fiber length/width and their distributions, morphology, infrared spectroscopy, thermogravimetric analysis, H–nuclear magnetic resonance spectra, and C–nuclear magnetic resonance spectra of cellulose fibers before and after the accelerated aging. The durability, properties, and mechanism of the fire-resistant “Xuan paper” based on ultralong HAP nanowires during the accelerated aging were studied. The experiments reveal the reasons for the deteriorated properties and reduced durability by aging of the traditional Xuan paper based on cellulose fibers, and the mechanism for the super-durability and excellent performances of the fire-resistant “Xuan paper” based on ultralong HAP nanowires during the accelerated aging process.